2010
DOI: 10.1371/journal.ppat.1000867
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Clearance of Translocated Bacterial Products in HIV-Infected Humanized Mice

Abstract: Bacterial translocation from the gut and subsequent immune activation are hallmarks of HIV infection and are thought to determine disease progression. Intestinal barrier integrity is impaired early in acute retroviral infection, but levels of plasma lipopolysaccharide (LPS), a marker of bacterial translocation, increase only later. We examined humanized mice infected with HIV to determine if disruption of the intestinal barrier alone is responsible for elevated levels of LPS and if bacterial translocation incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 55 publications
(56 reference statements)
3
47
0
Order By: Relevance
“…During remission, macrophage clearance may decrease, yet permeability remains; so higher serum LPS levels are observed in inactive disease, as we report here. This hypothesis is supported by evidence from a mouse model of colitis, 41 where intestinal epithelial damage alone did not result in an increase in blood LPS, but had to be coupled with a depletion of phagocytic cells. In the absence of LPS-scavenging mucosal cells 42 and Kupffer cells of the liver, 40,41 LPS levels in plasma are increased.…”
Section: Discussionmentioning
confidence: 74%
“…During remission, macrophage clearance may decrease, yet permeability remains; so higher serum LPS levels are observed in inactive disease, as we report here. This hypothesis is supported by evidence from a mouse model of colitis, 41 where intestinal epithelial damage alone did not result in an increase in blood LPS, but had to be coupled with a depletion of phagocytic cells. In the absence of LPS-scavenging mucosal cells 42 and Kupffer cells of the liver, 40,41 LPS levels in plasma are increased.…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, we showed that chronic HIV infection in HIV-infected humanized mice results in an increased rate of bacterial translocation, which is most likely at the origin of the malfunctioning of macrophages observed in this model (16).…”
mentioning
confidence: 74%
“…The TLR-dependent reduction in endocytosis is reminiscent of a proposed vitamin D-and cyclic AMP-dependent autophagic mechanism that apparently inhibits HIV replication in response to a TLR8 agonist (30). Reduced endocytosis is also observed in macrophages from HIV-infected humanized mice (16). The finding that endocytosis in M2-polarized or TLR2 agonistprimed macrophages was similar to that in MDMs suggests that endocytosis most likely has no role in the anti-HIV effects in this setting.…”
Section: Figmentioning
confidence: 93%
“…This suggests that in vitro mitogenic stimulation generates cells with an activated phenotype without altering the CD4:CD8 ratios. In a more relevant in vivo model, Hofer et al (42) demonstrated that experimental induction of intestinal damage and microbial translocation in humanized mice resulted in immune activation but failed to alter CD4:CD8 ratio or induce a specific loss of CD4+ T cells.…”
Section: Resultsmentioning
confidence: 99%